Urate and risk of Alzheimer's disease and vascular dementia: A population‐based study. Issue 6 (2nd May 2019) - Scheepers, Lieke E.J.M.; Jacobsson, Lennart T.H.; Kern, Silke; Johansson, Lena; Dehlin, Mats; Skoog, Ingmar
Abstract: Introduction: Low serum urate (sU) has been suggested to increase the risk of dementia since a reduction might impair antioxidant capacity. On the other hand, high sU is associated with increased cardiovascular risk which might increase the risk of dementia, especially for vascular dementia. Methods: In 1968–1969, a population‐based sample of 1462 women aged 38 to 60 years was examined and were followed up over 44 years (mean 33.1 years). We examined whether sU (determined in 1968–1969 and 1992–1994) is associated with risk of late‐life dementia. Results: During 44 years of follow‐up, a higher sU (per standard deviation of 76.5 μmol/L) was associated with lower risk for dementia (n = 320; hazard ratio [HR] 0.81; confidence interval [CI] 0.72–0.91), Alzheimer's disease (n = 152; HR 0.78; CI 0.66–0.91), and vascular dementia (n = 52; HR 0.66; CI 0.47–0.94). Discussion: Our findings support the hypothesis that sU has a protective role in the development of dementia, regardless of dementia subtype. This may have important implications in the treatment of dementia and treatment goals for hyperuricemia in patients with gout.